2008
DOI: 10.1086/595744
|View full text |Cite
|
Sign up to set email alerts
|

CRISP Spectropolarimetric Imaging of Penumbral Fine Structure

Abstract: We discuss penumbral fine structure in a small part of a pore, observed with the CRISP imaging spectropolarimeter at the Swedish 1-m Solar Telescope (SST), close to its diffraction limit of 0.16 arcsec. Milne-Eddington inversions applied to these Stokes data reveal large variations of field strength and inclination angle over dark-cored penumbral intrusions and a dark-cored light bridge. The mid-outer part of this penumbra structure shows 0.3 arcsec wide spines, separated by 1.6 arcsec (1200 km) and associated… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
391
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 416 publications
(395 citation statements)
references
References 17 publications
4
391
0
Order By: Relevance
“…Rouppe van der Voort et al, 2009;Sekse, Rouppe van der Voort, and De Pontieu, 2012;Pereira et al, 2014) that the RBEs observed in profiles of different chromospheric lines are on-disk counter parts of solar spicules. In addition, it is also reported that the doppler velocity of RBEs increases along their length in CHs when observed in the 8542Å (Ca II) spectral line using the CRisp Imaging SpectroPolarimeter instrument (CRISP, Scharmer et al (2008)) at the Swedish 1-m Solar Telescope (SST). However, no such trend was observed for QS RBEs (see Sekse et al, 2013 for detailed discussion).…”
Section: Resultsmentioning
confidence: 99%
“…Rouppe van der Voort et al, 2009;Sekse, Rouppe van der Voort, and De Pontieu, 2012;Pereira et al, 2014) that the RBEs observed in profiles of different chromospheric lines are on-disk counter parts of solar spicules. In addition, it is also reported that the doppler velocity of RBEs increases along their length in CHs when observed in the 8542Å (Ca II) spectral line using the CRisp Imaging SpectroPolarimeter instrument (CRISP, Scharmer et al (2008)) at the Swedish 1-m Solar Telescope (SST). However, no such trend was observed for QS RBEs (see Sekse et al, 2013 for detailed discussion).…”
Section: Resultsmentioning
confidence: 99%
“…On one hand, Schrijver (2001), using various channels of TRACE, has estimated the occurrence rate of coronal rain in active region loops to be at most once every two days, suggesting a sporadic character for the phenomenon. On the other hand, in Hα observations at the limb with the CRisp Imaging SpectroPolarimeter (CRISP, Scharmer et al 2008), at the Swedish 1-m Solar Telescope (SST, Scharmer et al 2003a), Antolin and Rouppe van der Voort (2012) present a ubiquitous character of coronal rain, and show that it is composed of a myriad of small blobs, with sizes that are, on average, 300 km in width and 700 km in length. Furthermore, if close enough together and in large enough quantities, the blobs are seen as large clumps termed 'showers'.…”
mentioning
confidence: 99%
“…We obtained a series of observations at the Swedish 1 m Solar Telescope (SST; Scharmer et al 2003) on La Palma using the Crisp Imaging SpectroPolarimeter (CRISP; Scharmer et al 2008) instrument. CRISP is a dual Fabry-Pérot interferometer (FPI) that contains three high-speed CCD cameras (35 frames s −1 with an exposure time of 17 ms per frame): two cameras behind the FPI and a polarizing beam splitter, and a third "wide band" camera located before the FPI, which is used as an anchor channel for image processing.…”
Section: Observationsmentioning
confidence: 99%